Prevalence and unfavourable outcome of oral frailty in older adult: a systematic review and meta-analysis - Zhu, Sheng-Rui; Wei, Liu-Ying; Jia, Kui; Xie, Yuan-Xi; Tan, Zheng-Ke-Ke; Mo, Shu-Tian; Tang, Wen-Zhen (Frontiers in Public Health, 2024)
Background and objectiveOral frailty (OF) refers to a decline in oral function amongst older adult that often occurs alongside declines in cognitive and physical abilities. We conducted a study to determine the prevalence and unfavourable outcomes of OF in the older adult population to provide medical staff with valuable insights into the associated disease burden.MethodsFrom inception to March 2024, we systematically searched six key electronic databases: PubMed, Web of Science, Embase, Cochrane Library, Scopus, and CINAHL to identify potential studies that reported the prevalence or unfavourable outcomes of OF amongst older adult. Studies that did not have accessible data were excluded. Two researchers worked independently to retrieve the literature, collect data, and evaluate the quality of the included studies. Data analysis was conducted using R Project 4.1.1 and Review Manager 5.3 software.ResultsWe identified 28 studies that met the inclusion criteria, including 27,927 older adult. The pooled prevalence of OF amongst older adult was 32% (95% confidence interval (CI): 0.24, 0.41). Subgroup analyses indicated that the setting, sample, design of studies, and assessment instruments influence the prevalence of OF. In addition, OF was associated with a high risk of physical frailty (odds ratio (OR) = 1.67; 95% CI: 1.38, 2.02), malnutrition (OR = 2.27; 95% CI: 1.75, 2.96), low dietary variety (OR = 1.98, 95% CI: 1.15, 3.39), and social withdrawal (OR = 1.42; 95% CI: 1.18, 1.71).ConclusionThis systematic review and meta-analysis revealed that OF is prevalent amongst older adult. OF may affect the prognosis of older adult and thus necessitates comprehensive assessment and management as part of an integrated approach.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=537884.